Fruit and vegetable consumption is associated with improved mental and cognitive health in older adults from non-Western developing countries - Gehlich, Kerstin H; Beller, Johannes; Lange-Asschenfeldt, Bernhard; Köcher, Wolfgang; Meinke, Martina C; Lademann, Jürgen (Public health nutrition, 2019)
Consumption of fruits and vegetables has been shown to contribute to mental and cognitive health in older adults from Western industrialized countries. However, it is unclear whether this effect replicates in older adults from non-Western developing countries. Thus, the present study examined the contribution of fruit and vegetable consumption to mental and cognitive health in older persons from China, India, Mexico, Russia, South Africa and Ghana. Representative cross-sectional and cross-national study.Setting/SubjectsWe used data from the WHO Study on Global Ageing and Adult Health (SAGE), sampled in 2007 to 2010. Our final sample size included 28 078 participants. Fruit and vegetable consumption predicted an increased cognitive performance in older adults including improved verbal recall, improved delayed verbal recall, improved digit span test performance and improved verbal fluency; the effect of fruit consumption was much stronger than the effect of vegetable consumption. Regarding mental health, fruit consumption was significantly associated with better subjective quality of life and less depressive symptoms; vegetable consumption, however, did not significantly relate to mental health. Consumption of fruits is associated with both improved cognitive and mental health in older adults from non-Western developing countries, and consumption of vegetables is associated with improved cognitive health only. Increasing fruit and vegetable consumption might be one easy and cost-effective way to improve the overall health and quality of life of older adults in non-Western developing countries.